2023
DOI: 10.3390/w15081625
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Empirical Mode Decomposition and a Long Short-Term Memory Neural Network for Surface Water Quality Prediction of the Xiaofu River, China

Abstract: Water quality prediction is an important part of water pollution prevention and control. Using a long short-term memory (LSTM) neural network to predict water quality can solve the problem that comprehensive water quality models are too complex and difficult to apply. However, as water quality time series are generally multiperiod hybrid time series, which have strongly nonlinear and nonstationary characteristics, the prediction accuracy of LSTM for water quality is not high. The ensemble empirical mode decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this study, the Daubechies-4 (db4) mother wavelet was utilized to perform a three-level decomposition of the original time series, a choice popular for its widespread acceptance and efficient performance [26]. The ensemble number of the EEMD model was set to 100, and the standard deviation of Gaussian white noise, n i (t), was 0.05 [30]. We set the window length of the SSA to 15 according to the empirical evaluation of component contributions in the experiment.…”
Section: Model Implementationmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, the Daubechies-4 (db4) mother wavelet was utilized to perform a three-level decomposition of the original time series, a choice popular for its widespread acceptance and efficient performance [26]. The ensemble number of the EEMD model was set to 100, and the standard deviation of Gaussian white noise, n i (t), was 0.05 [30]. We set the window length of the SSA to 15 according to the empirical evaluation of component contributions in the experiment.…”
Section: Model Implementationmentioning
confidence: 99%
“…This is in line with the previous study by Liu et al [26], who demonstrated that the decomposition-based hybrid WT-LSTM model could enhance the fitting of abrupt or extreme data points and improve HAB prediction performance. Likewise, Luo et al [30] developed a hybrid EEMD-LSTM model for predicting water quality, and the results demonstrated that the proposed model outperformed the individual LSTM model in various evaluation indicators. Cui et al [42] also discovered that integrating SSA with a lightweight gradient-boosting machine in a hybrid model led to high-accuracy, real-time predictions of urban runoff.…”
Section: Evaluating the Predictive Performance Of Deep Learning Based...mentioning
confidence: 99%
See 3 more Smart Citations